The Relationship Between Food Consumption and Bowel Symptoms Among Patients With Rectal Cancer After Sphincter-Saving Surgery - Liu, Wen; Xu, Jian Min; Zhang, Yu Xia; Lu, Hui Juan; Xia, Hai Ou (Frontiers in Medicine, 2021)
Dietary self-management is an important strategy for controlling bowel symptoms after sphincter-saving surgery; however, the dietary factors influencing bowel symptoms are not completely clear. This study aimed to explore the relationship between the specific consumption of food components and bowel symptoms. This study applied a cross-sectional study design. Using convenience sampling, a total of 169 patients with rectal cancer after sphincter-saving surgery were selected from a tertiary hospital. Data were collected through three questionnaires, including general and treatment-related questionnaires, the Memorial Sloan Kettering Cancer Center (MSKCC) bowel function scale-Chinese version and the food frequency questionnaire. Multiple linear regression analysis was used to analyze the collected data. It was found that the consumptions of fruit, cholesterol, and protein and the interaction of cereals and milk products were the main dietary factors affecting bowel symptoms in patients after sphincter-saving surgery. The consumption of protein and fruit was negatively correlated with the symptoms of frequent and urgent defecation, and the consumption of fruit and protein was negatively correlated with general bowel function. The consumption of fruit was negatively correlated with the abnormal feeling of defecation and the interaction between cereals and milk products was positively correlated with the abnormal feeling of defecation. The results of this study provide evidence for medical staff to further develop scientific dietary education programs to relieve bowel symptoms and promote the quality of life of patients in the future. More research is also needed to explore the mechanisms of the effects of different food components on bowel symptoms in patients after sphincter-saving surgery in the future.